The Modern Essence and Composition of the Mechanism of Public Regulation of the Corporatization of Large State-Owned Enterprises in the Transport Infrastructure Sector - Gromov, Serhiy (Theory and Practice of Public Administration, 2024)
The paper aims to clarify the contemporary essence and component structure of the public regulation mechanism for the corporatization of large state-owned enterprises in Ukraine’s transport infrastructure sector. The author draws an important conclusion that the transformation of the public management mechanism for the corporatization of large state-owned enterprises in Ukraine under the influence of digital technologies is an inevitable process that corresponds to global trends in the development of the public sector and the demands of modern society. This evolution aims to optimize the management of public values and promote a collaborative approach to decision-making. A key aspect of this transformation is the integration of big data and artificial intelligence technologies into the processes of analysis and forecasting of state-owned enterprises’ activities. This will enable the creation of more accurate and objective models for assessing the effectiveness of their functioning and predicting potential risks and opportunities. Thus, the corporatization process will become more transparent and substantiated, which will increase public trust in state institutions. The implementation of value-based management based on public value management and collaborative governance in the activities and public management of large state-owned enterprises in the transport sector (e.g., JSC “Ukrzaliznytsia” and SE “AMPU”) will signify a substantial transformation of approaches to the functioning of this strategically important enterprise. This paradigm shift goes far beyond traditional corporate governance and linear management, creating a new model of interaction between the state, the enterprise, and society.